2022
DOI: 10.3390/ijms231911858
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in Women with Schizophrenia Is Associated with Lower HDL Cholesterol Levels

Abstract: This study assessed the association between serum lipid levels and aggression in female patients with schizophrenia. The study included female patients with schizophrenia (N = 120). The participants were subdivided into two groups (aggressive and nonaggressive), with 60 participants in each group. Serum lipids—cholesterol, triglycerides, high-density lipoproteins (HDL cholesterol), and low-density lipoproteins (LDL cholesterol)—were determined. The clinical part of the study included an evaluation using psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…In [39]. Additionally, lower HDL levels have been associated with SCZ and psychosis in various studies [40][41][42]. Consistent with this, we observed negative genetic correlations between HDL and SCZ.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In [39]. Additionally, lower HDL levels have been associated with SCZ and psychosis in various studies [40][41][42]. Consistent with this, we observed negative genetic correlations between HDL and SCZ.…”
Section: Discussionsupporting
confidence: 90%
“…Notably, Liang et al reported that low HDL levels may be linked to more severe depressive symptoms in East Asian populations [39]. Additionally, lower HDL levels have been associated with SCZ and psychosis in various studies [4042]. Consistent with this, we observed negative genetic correlations between HDL and SCZ.…”
Section: Discussionsupporting
confidence: 89%
“…Herceg et al pointed out that in female schizophrenia patients, lowered HDL cholesterol levels have been associated with aggression. 25 Another study showed that higher prolactin was significantly associated with aggression in female schizophrenia patients. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Herceg et al pointed out that in female schizophrenia patients, lowered HDL cholesterol levels have been associated with aggression. 25 Another study showed that higher prolactin was significantly associated with aggression in female schizophrenia patients. 26 Persons with schizophrenia frequently experience depressive mood, and a meta-analysis including 9879 persons with schizophrenia indicated that the frequency of co-morbid depression in schizophrenia was about 28.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, research has highlighted that lipoprotein metabolism’s role extends beyond the metabolic side effects in schizophrenia to include the disorder’s psychiatric symptoms. For instance, a study identified a strong link between low HDL serum levels and increased aggression in female schizophrenia patients ( Herceg et al, 2022 ). In contrast, another study observed that rising serum HDL levels during the first year of antipsychotic treatment corresponded with reduced negative symptoms ( Gjerde et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%